Socio-Economic Domain Assessment of the EAFM Approach in the Bullet Tuna Fishery at Prigi Nusantara Fishing Port (PPN), Trenggalek, East Java - Anggita Nur Aguspriyani; I Wayan Restu; Suprabadevi Ayumayasari Saraswati; I Ketut Wija Negara (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2026)
The capture fisheries landed at the Nusantara Fishing Port (PPN) in Prigi, Trenggalek, East Java, play a strategic role in influencing the social and economic conditions of fishing households. The production of bullet tuna is highly volatile, which in turn impacts these socio-economic conditions. This study aims to analyze the assessment of the social and economic domains in the implementation of EAFM for the bullet tuna fishery at PPN Prigi. It employs a qualitative method using the Ecosystem Approach to Fisheries Management (EAFM), which integrates social and economic aspects as a potential solution to achieve sustainable fisheries management and improve fishers' welfare. Data collection techniques included field observations and interviews with 98 fishers who use purse seine and Danish seine gear. The findings indicate that the social domain is rated as 'good' with a composite score of 66. This rating is characterized by a low potential for conflict, which is crucial to maintain, although stakeholder participation and the utilization of local knowledge are not yet optimal. The economic domain was classified as